2022
DOI: 10.1021/acs.biochem.2c00422
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Histone H2B Ubiquitylations on the Nucleosome Structure and Internucleosomal Interactions

Abstract: Eukaryotic gene compaction takes place at multiple levels to package DNA to chromatin and chromosomes. Two of the most fundamental levels of DNA packaging are at the nucleosome and dinucleosome stacks. The nucleosome is the basic gene-packing unit and is composed of DNA wrapped around a histone core. Nucleosomes stack with one another for further compaction of DNA. The first stacking step leads to dinucleosome formation, which is driven by internucleosomal interactions between various parts of two nucleosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(115 reference statements)
1
3
0
Order By: Relevance
“…These results suggest that the effects of H2BK34ub on transcription kinetics can be the major mechanisms of facilitated transcription by H2B ubiquitylations. The effects are likely due to localized perturbations of the nucleosome structure near the DNA-(H2B-H2B) contact region, which has been validated by our recent structural study based on smFRET 56 . We suspect that the weaker effects of H2BK120ub is due to its non-ideal location to affect DNA-histone interactions.…”
Section: Discussionsupporting
confidence: 61%
“…These results suggest that the effects of H2BK34ub on transcription kinetics can be the major mechanisms of facilitated transcription by H2B ubiquitylations. The effects are likely due to localized perturbations of the nucleosome structure near the DNA-(H2B-H2B) contact region, which has been validated by our recent structural study based on smFRET 56 . We suspect that the weaker effects of H2BK120ub is due to its non-ideal location to affect DNA-histone interactions.…”
Section: Discussionsupporting
confidence: 61%
“… Since then, it has been shown that H2BK34ub nucleosomes have the ubiquitin moieties protrude between the two gyres of the nucleosomal DNA, weakening the structural integrity of the nucleosome and distorting DNA toward the entry region of the nucleosome. , These results suggest that the effects of H2BK34ub on transcription kinetics can be the major mechanisms of facilitated transcription by H2B ubiquitylations. The effects are likely due to localized perturbations of the nucleosome structure near the DNA–(H2B-H2B) contact region, which has been validated by our recent structural study based on smFRET . We suspect that the weaker effects of H2BK120ub are due to its nonideal location to affect DNA–histone interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, affinity of nucleosomes to positioning sequences can prevent the assembly of nucleosome clusters. It has also been discussed 47 that the relaxed DNA− (H2A−H2B) region may contribute to long-range internucleosomal interactions between DNA and histone tails. Therefore, the decrease in the binding between DNA and histone octamers on the nonspecific substrate compared to that on the 601 sequence benefits the long-range internucleosomal interactions and, ultimately, the compaction of the oligonucleosomes.…”
Section: ■ Discussionmentioning
confidence: 99%